2010
DOI: 10.1007/s00425-010-1247-1
|View full text |Cite
|
Sign up to set email alerts
|

The 3′ untranslated region of the two cytosolic glutamine synthetase (GS1) genes in alfalfa (Medicago sativa) regulates transcript stability in response to glutamine

Abstract: Glutamine synthetase (GS) catalyzes the ATP-dependent condensation of ammonia with glutamate to produce glutamine. The GS enzyme is located either in the chloroplast (GS(2)) or in the cytoplasm (GS(1)). GS(1) is encoded by a small gene family and the members exhibit differential expression pattern mostly attributed to transcriptional regulation. Based on our recent finding that a soybean GS(1) gene, Gmglnβ ( 1 ) is subject to its 3'UTR-mediated post-transcriptional regulation as a transgene in alfalfa (Medicag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 55 publications
1
8
0
Order By: Relevance
“…The data presented here, points to the 5′ UTR of the Gm glnβ 1 gene as the determinant of translation enhancement and confirms our earlier finding that the 3′UTR of the Gm glnβ 1 gene controls the turnover of the transcript (Ortega et al 2006; Simon and Sengupta-Gopalan 2010). In this study, a transient assay using agroinfiltration has allowed us to simultaneously check the expression of different gene constructs involving the 5′ and 3′UTRs of the Gm glnβ 1 gene at the level of transcript and protein accumulation.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The data presented here, points to the 5′ UTR of the Gm glnβ 1 gene as the determinant of translation enhancement and confirms our earlier finding that the 3′UTR of the Gm glnβ 1 gene controls the turnover of the transcript (Ortega et al 2006; Simon and Sengupta-Gopalan 2010). In this study, a transient assay using agroinfiltration has allowed us to simultaneously check the expression of different gene constructs involving the 5′ and 3′UTRs of the Gm glnβ 1 gene at the level of transcript and protein accumulation.…”
Section: Discussionsupporting
confidence: 91%
“…We have found that regulation of expression of a soybean ( Glycine max ) GS 1 gene (Gm glnβ 1 ) driven by a constitutive promoter (CaMV 35S) in transgenic plants occurs at a post-transcriptional level (Ortega et al 2001, 2006). We have also shown that the post-transcriptional regulatory step of the Gm glnβ 1 and the GS 1 genes from alfalfa is, at the level of transcript turnover, mediated by their 3′UTR (Ortega et al 2006; Simon and Sengupta-Gopalan 2010). The goal of this study was to investigate if Gm glnβ 1 is also subject to other modes of regulation by testing the role of its 5′UTR in the regulation of gene expression.…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…The 3'-UTR, located between the stop codon and the poly(A) tail, may possess a variety of regulatory mechanisms. The 3'-UTRs of the two cytosolic glutamine synthetase genes were characterized as regulators of transcript stability in response to glutamine in Medicago sativa (Simon and Sengupta-Gopalan 2010). Splicing and alternative 3' end processing of mRNAs mediate riboswitch control of gene expression in plants (Wachter et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…The regulation of GS 1 gene expression is not limited to transcription (Sengupta‐Gopalan & Ortega, ). It has been shown that GS 1 is regulated at the level of transcript stability, mediated by its 3′UTR (Ortega et al., ; Simon & Sengupta‐Gopalan, ) and at the translational level by the 5′UTR (Ortega, Wilson, & Sengupta‐Gopalan, ). Furthermore, GS is subject to extensive posttranslational modification like phosphorylation (Finnemann & Schjoerring, ; Lima, Seabra, Melo, Cullimore, & Carvalho, ), ubiquitination, and binding with other proteins (Seabra, Silva, & Carvalho, ).…”
Section: Introductionmentioning
confidence: 99%